International Capital Flows, External Assets and Output Volatility - Matthias Hoffmann; Michael Krause; Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
This paper proposes a new perspective on international capital flows and countries' long-run external asset position. Cross-sectional evidence for 84 developing countries shows that over the last three decades countries that have had on average higher volatility of output growth (1) accumulated higher external assets in the long-run and (2) experienced more procyclical capital outflows over the business cycle than those countries with a same growth rate but a more stable output path. To explain this finding we provide a theoretical mechanism within a stochastic real business cycle growth model in which higher uncertainty of the income stream increases the precautionary savings motive of households. They have a desire to save more when the variance of their expected income stream is higher. We show that in the model the combination of income risk and a precautionary savings motive will lead to procyclical capital outflows at business cycle frequency and a higher long-run external asset position.
Keywords: F32; F36; F43; F44; 330; Capital flows; net foreign assets; productivity growth; uncertainty; precautionary savings